GRAIN GROWTH IN PARTIALLY MOLTEN OLIVINE AGGREGATES - Faul U.H.; Scott D. (My University, 2006)
Grain growth rates in partially molten olivine aggregates were determined experimentally at a pressure of 1GPa. The aim of the experiments with fine-grained starting material (solution-gelation derived Fo90 olivine with a grain size of ~1 μm with 2 and 4 wt.% added basaltic glass) was to determine growth rates during steady-state grain growth. A series of experiments was conducted at a fixed temperature of 1,350°C for durations from 2 to 700 h, and a second series at fixed duration (168 h) at temperatures from 1,250 to 1,450°C. The resulting activation energy (E = 390 kJ/mol) and growth exponent (n = 4.3) are comparable to melt-free results (Nichols and Mackwell 1991. The observed grain size distributions are broader than those predicted for normal grain growth or Ostwald ripening and most similar to the Log-normal distribution. The observed melt distribution is influenced by the continuous rearrangement of neighboring grains during growth. The relatively large growth exponent observed in this study and by Nichols and Mackwell 1991 where secondary phases are present suggests that grain growth in the upper mantle is slower than predicted by Karato (1989). © Springer-Verlag 2005.
Keywords: GRAIN GROWTH; OLIVINE; PARTIALLY MOLTEN ROCKS